Analisis Hukum Tentang Kepentingan Umum Menurut Pasal 310 Ayat (3) KUHP di Indonesia sebagai Alasan Penghapusan Pidana dalam Kegiatan Pers - Aditya Pranata Kaban; M. Hamdan; Budiman Ginting; Mahmud Mulyadi (Universitas Sumatera Utara, 2022)
The public interest is the foundation of any norms and rules of law in force in the Republic of Indonesia. It’s because the public interest is most important than others, such as the interests of the state, the interest of a group, and the interests of the individual, after that the public interest is the reason for removing the offense if it can be proved that the punishable act was done in the public interests, in accordance with Article 310 Paragraph (3) of the Criminal Code. As we all know the activities of the Press often cause problems where the press is considered a crime to make